Microbial eukaryote diversity in the marine oxygen minimum zone off northern Chile - Parris, Darren J.; Ganesh, Sangita; Edgcomb, Virginia P.; DeLong, Edward F.; Stewart, Frank J. (Frontiers in Microbiology, 2014)
Molecular surveys are revealing diverse eukaryotic assemblages in oxygen-limited ocean waters. These communities may play pivotal ecological roles through autotrophy, feeding, and a wide range of symbiotic associations with prokaryotes. We used 18S rRNA gene sequencing to provide the first snapshot of pelagic microeukaryotic community structure in two cellular size fractions (0.2-1.6 µm, >1.6 µm) from seven depths through the anoxic oxygen minimum zone (OMZ) off northern Chile. Sequencing of >154,000 amplicons revealed contrasting patterns of phylogenetic diversity across size fractions and depths. Protist and total eukaryote diversity in the >1.6 µm fraction peaked at the chlorophyll maximum in the upper photic zone before declining by 50% in the OMZ. In contrast, diversity in the 0.2-1.6 µm fraction, though also elevated in the upper photic zone, increased four-fold from the lower oxycline to a maximum at the anoxic OMZ core. Dinoflagellates of the Dinophyceae and endosymbiotic Syndiniales clades dominated the protist assemblage at all depths ( 40-70% of sequences). Other protist groups varied with depth, with the anoxic zone community of the larger size fraction enriched in euglenozoan flagellates and acantharean radiolarians (up to 18% and 40% of all sequences, respectively). The OMZ 0.2-1.6 µm fraction was dominated (11-99%) by Syndiniales, which exhibited depth-specific variation in composition and total richness despite uniform oxygen conditions. Metazoan sequences, though confined primarily to the 1.6 µm fraction above the OMZ, were also detected within the anoxic zone where groups such as copepods increased in abundance relative to the oxycline and upper OMZ. These data, compared to those from other low-oxygen sites, reveals variation in OMZ microeukaryote composition, helping to identify clades with potential adaptations to oxygen-depletion.